Minutes of collegiate bodies: new dispositions for the office administration professional - Solís Chaverri, Brandon (2024)
This article focuses on a review of the literature related to the new guidelines for the preparation of minutes.  The main objective of this study is to analyze the legislative and regulatory changes implemented in Costa Rica, as well as the incorporation of technology in the management of collegiate bodies and the documentation associated with their work. The research is framed within the hermeneutic paradigm and was developed through a documentary review model that involved the compilation and thorough analysis of various bibliographic sources.  Among the results found, it is highlighted that the legislative and regulatory changes have significantly transformed the dynamics of the drafting and format of this document, which requires a continuous training process for office administration professionals. One of the most relevant findings highlights the importance of administrative transparency for the proper management of organizations, in which the minutes play a crucial role as a document that evidences what was discussed and agreements made in the collegial bodies. It also emphasizes the existence of new provisions regulating the drafting and format of the minutes.